2018
DOI: 10.1136/bjophthalmol-2017-311746
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and causes of vision loss in Latin America and the Caribbean in 2015: magnitude, temporal trends and projections

Abstract: These prevalence estimates indicate that one in five persons across LAC had some degree of vision loss in 2015. We predict that from 2015 to 2020, the absolute numbers of persons with vision loss will increase by 12% to 132.33 million, while the all-age age-standardised prevalence will decrease for blindness by 15% and for other distance vision impairment by 8%. All countries need epidemiologic research to establish accurate national estimates and trends. Universal eye health services must be included in unive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 18 publications
(32 reference statements)
0
13
0
4
Order By: Relevance
“…It has been suggested that visual impairment compromises the ability to avoid obstacles, being cataracts and refractive error the most frequent cause of visual impairment among older people [6][7][8]. Age-associated cataracts remain the leading cause of visual impairment and blindness in lowand middle-income countries, including Latin America [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that visual impairment compromises the ability to avoid obstacles, being cataracts and refractive error the most frequent cause of visual impairment among older people [6][7][8]. Age-associated cataracts remain the leading cause of visual impairment and blindness in lowand middle-income countries, including Latin America [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Cataract is one of the most common causes of blindness on all continents [1][2][3][4][5][6][7]. Various surgical treatments are available to help patients recover from the disease.…”
Section: Introductionmentioning
confidence: 99%
“…5 In terms of its overall contribution to blindness, a series of regional reports estimate glaucoma's contribution to blindness in 2015 to range between 6% (South Asia) to 16% (Sub-Saharan Africa), while for vision impairment (<6/18 to 3/60 presenting visual acuity in the better eye), its contribution ranged between 1% (South Asia) to 4% (Sub-Saharan Africa). [6][7][8][9][10][11] It is important to note that these models consider only the cases of glaucoma that reduce visual acuity below 6/18 in the better eye with no consideration given to severity of visual field loss in the definition. Therefore these estimates very much underestimate the full 'burden' of disability or impact on quality of life caused by glaucoma.…”
Section: Text Of Reviewmentioning
confidence: 99%